Chimpanzees, sorcery and contestation in a protected area in Guinea‐Bissau. (31st May 2017) - Sousa, Joana; Hill, Catherine M.; Ainslie, Andrew
Abstract : In Cantanhez National Park in Guinea‐Bissau the construction of meaning made after encounters with chimpanzees is associated with local social life. If a chimpanzee makes an unprovoked attack on a person, its actions are often understood as those of a sorcerer. Chimpanzees are involved in two parallel accusation discourses: one is played in intimate spheres of sociability where sorcerers harm their kin to benefit from secret alliances, and the other addresses a wider audience perceived to benefit from chimpanzees which are being protected at the expense of other humans. Both narratives represent local criticism against transgressions to calculations of redistribution and reciprocity.